Angle-specific impairment of elbow flexors strength after isometric exercise at long muscle length - Philippou, A.; M Maridaki; Bogdanis, G.C. (Journal of Sports Sciences, 2003)
In this study, we examined the long-term reductions in maximal isometric force (MIF) caused by a protocol of repeated maximal isometric contractions at long muscle length. Furthermore, we wished to ascertain whether the reductions in MIF are dependent on muscle length - that is, are the reductions in MIF more pronounced when the muscle contracts at a short length. The MIF of the elbow flexors of seven young male volunteers was measured at five different elbow angles between 50° and 160°. On a separate day, the participants performed 50 maximal voluntary isometric muscle contractions with the elbow flexors at a lengthened position; that is, with the shoulder hyperextended at 45° and the elbow joint fixed at 140°. Following this exercise, the MIF at the five elbow angles, range of motion, muscle soreness and plasma creatine kinase activity were measured at 24 h intervals for 4 days. On day 1, the decline in MIF was higher at the more acute elbow angles of 50° (42 ± 8%) and 70° (39 ± 8%; both P < 0.01) than at 90° (26 ± 4%) and 140° (16 ± 3%; both P < 0.01). No significant reduction in MIF was evident at an elbow angle of 160°. Maximal isometric force at an elbow angle of 140° was fully restored on day 3, whereas at an angle of 50° it remained depressed for the 4 day observation period. Restoration of MIF was a function of the elbow angle, with force recovery being less at the smaller angles. The range of motion was decreased by 14 ± 2° on day 1 (P < 0.01) and did not return to baseline values by day 4. Muscle soreness ratings remained significantly elevated for the 4 day period. Serum creatine kinase peaked on day 1 (522 ± 129 IU, P < 0.01) and decreased thereafter. We conclude that the disproportionate decrease in MIF at the small elbow angles and the length-specific recovery in MIF after repeated maximal isometric contractions at long muscle length may be explained by the presence of overstretched sarcomeres that increased in series compliance of the muscle, therefore causing a rightward shift of the force-length relationship.
Keywords: Creatine kinase; Length-force relationship; Muscle contractile function; Muscle damage